THE INFLUENCE OF STRESS EFFECTS AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT PT BANK RAKYAT INDONESIA TBK, PANAKKUKANG MAKASSAR BRANCH - Ismi, Nurul; Musa, Muh Ichwan; Dipoatmojo, Tenri S. P.; Tawe, Amiruddin; Haeruddin, Ikhwan Maulana (Transpublika Publisher, 2023)
Work stress, often arising from factors such as heavy workloads, tight deadlines, and interpersonal conflicts, can negatively impact employees' mental and physical health, job satisfaction, and overall job performance. High levels of work stress can lead to decreased motivation, increased absenteeism, and reduced productivity, which can ultimately affect an organization's bottom line. On the other hand, job satisfaction is a measure of how content employees are with their work and the work environment. When employees are satisfied with their jobs, they tend to be more engaged, motivated, and committed to their tasks, leading to higher job performance and overall organizational success. Job satisfaction is influenced by various factors, including job security, recognition, work-life balance, and opportunities for growth and development. This study aims to determine the effects of work stress (X1) and job satisfaction (X2) on the performance (Y) of PT Bank Rakyat Indonesia Tbk, Panakkukang Makassar Branch. The research type employed is descriptive quantitative. The study's population consists of all employees at PT Bank Rakyat Indonesia Tbk, which includes 73 branches in Panakkukang Makassar. The sample size comprises 73 employees. Data collection was conducted using a questionnaire. Data analysis involved simple regression analysis using SPSS Version 25 in 2023. The results indicate that work stress has no positive and significant effect on performance; when work stress increases, employee performance decreases, and vice versa. Conversely, job satisfaction has a positive and significant impact on performance. When individuals experience higher job satisfaction, it leads to improved performance.